Pharmacological Profiles of the Novel Analgesic M58996 in Rat Models of Persistent and Neuropathic Pain - Yasushige Akada; Reiko Mori; Kazuyuki Matsuura; Kazuhiro Suzuki; Kazuo Kato; Masatsugu Kamiya; Hiroyasu Naba; Misao Kurokawa; Takuo Ogihara; Yutaka Kato; Fumiaki Yamasaki; Ichiro Yamamoto (Elsevier, 2006)
We investigated the effects of 4-(N-{1-[2-(4-cyanophenyl)ethyl]-4-hydroxypiperidin-4-ylmethyl}-N-methylamino)benzoic acid monohydrochloride (M58996), a novel analgesic, on persistent and neuropathic pain in rats. In the formalin test, oral M58996 (0.3 - 10 mg/kg) reduced nociceptive behaviors only in the late phase. In the neuropathic pain model, oral M58996 (1 - 10 mg/kg) attenuated mechanical allodynia and heat hyperalgesia in the nerve-injured paw without affecting normal responses of the uninjured paw. High doses (10 - 100 mg/kg) of oral M58996 did not influence normal motor function. Thus, M58996 had a wide dose range showing antinociceptive, antiallodynic, and antihyperalgesic effects without motor dysfunction. In addition, we studied the possible mechanisms involved in the M58996-induced antinociception. The antinociceptive effect of M58996 was reversed by intrathecal pertussis toxin, an inhibitor of the inhibitory- and other-GTP-binding protein (Gi/o protein), but not by subcutaneous naloxone, an opioid-receptor antagonist. This effect was also reversed by intracerebroventricular or intrathecal tropisetron, a 5-hydroxytryptamine3 (5-HT3)-receptor antagonist, and intraperitoneal bicuculline, a γ-aminobutyric acidA (GABAA)-receptor antagonist. These results suggest that M58996 produces its antinociceptive effect by a pertussis toxin-sensitive G protein mechanism. In addition, the GABA released by the activation of supraspinal and/or spinal 5-HT3 receptors is likely to contribute to the M58996-induced antinociception. Keywords:: neuropathic pain, allodynia, formalin test, 5-HT3 receptor, GABAA receptor